Working in the Stay Hotel Guimarães Centro: Business Tourism and its Importance for the Success of a Hotel Unit - Sousa, Bárbara Raquel Fernandes (2022)
This report refers to an internship that was carried out as part of the Master's Degree in Intercultural Studies for Business at the Instituto Superior de Contabilidade e Administração do Porto. It had a total duration of four hundred hours and took place between February 2022 and May 2022 at the Stay Hotel Guimarães Centro, a member of the national chain "Stay Hotels". The main objective of this report is to explain not only how the internship took place, i.e., to describe as best as possible all the activities carried out in it, but also to develop with special attention the organization and functioning of the hotel itself, as well as the knowledge that was acquired during the internship. This internship covered the departments of Front-Office (reception) and F&B (Food and Beverage).